Assessment of segmental myocardial blood flow and myocardial perfusion reserve by adenosine‐stress myocardial arterial spin labeling perfusion imaging. Issue 2 (2nd February 2017) - Yoon, Andrew J.; Do, Hung Phi; Cen, Steven; Fong, Michael W.; Saremi, Farhood; Barr, Mark L.; Nayak, Krishna S.
Abstract : Purpose: To determine the feasibility of measuring increases in myocardial blood flow (MBF) and myocardial perfusion reserve (MPR) on a per‐segment basis using arterial spin labeled (ASL) magnetic resonance imaging (MRI) with adenosine vasodilator stress in normal human myocardium. Materials and Methods: Myocardial ASL scans at rest and during adenosine infusion were incorporated into a routine 3T MR adenosine‐induced vasodilator stress protocol and were performed in 10 healthy human volunteers. Myocardial ASL was performed using single‐gated flow‐sensitive alternating inversion recovery (FAIR) tagging and balanced steady‐state free precession (bSSFP) imaging at 3T. A T 2 ‐prep blood oxygen level‐dependent (BOLD) SSFP sequence was used to concurrently assess segmental myocardial oxygenation with BOLD signal intensity (SI) percent change in the same subjects. Results: There was a statistically significant difference between MBF measured by ASL at rest (1.75 ± 0.86 ml/g/min) compared to adenosine stress (4.58 ± 2.14 ml/g/min) for all wall segments ( P < 0.0001), yielding a per‐segment MPR of 3.02 ± 1.51. When wall segments were divided into specific segmental myocardial perfusion territories (ie, anteroseptal, anterior, anterolateral, inferolateral, inferior, and inferoseptal), the differences between rest and stress regional MBF for each territory remained consistently statistically significant ( P < 0.001) after correcting for multiple comparisons. Conclusion: This study demonstrates the feasibility of measuring MBF and MPR on a segmental basis by single‐gated cardiac ASL in normal volunteers. Second, this study demonstrates the feasibility of performing the ASL sequence and T 2 ‐prepared SSFP BOLD imaging during a single adenosine infusion. Level of Evidence: 2 Technical Efficacy : Stage 1 J. MAGN. RESON. IMAGING 2017;46:413–420